Prediction of soil and water conservation structure impacts on runoff and erosion processes using SWAT model in the Northern Ethiopian highlands - Demelash, Nigus; Renschler, Chris; Holzmann, Hubert; Strohmeier, Stefan; Bayu, Wondimu; Zucca, Claudio; Ziadat, Feras; Klik, Andreas (Springer, 2017)
Land degradation due to soil erosion is a serious threat to the highlands of Ethiopia. Various soil and water conservation (SWC) strategies have been in use to tackle soil erosion. However, the effectiveness of SWC measures on runoff dynamics and sediment load in terms of their medium- and short-term effects has not been sufficiently studied.